OUTEURSKAP VAN 'HISTORIESE STELLE - Otto, W. (Scientia Militaria - South African Journal of Military Studies, 2012)
The writer of the article wishes to allert the historiographer, to the many pitfalls that may accost him in his search for the truth. Sources must at all times be regarded critically, if the acceptance of untruths is to be avoided. The example quoted and discussed, is that of Gustav S. Preller's 'Historiese Opstelle no 9'.